(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Abubakar H, Astuti RI, Listyowati S, Batubara I, Wahyudi AT. 2022. An orange pigment from the marine bacterium Paracoccus haeundaensis SAB E11 as a prospective source of natural antioxidants. Biodiversitas 23: 4730-4737. Bacterial pigment extracts are the source of many natural antioxidant substances. The present study aimed to assess the antioxidant activity of an orange pigment derived from a marine bacterium, identified as Paracoccus haeundaensis SAB E11, analyzed by 2,2-diphenyl-1-picrylhydrazyl (DPPH) and 2,2-azino-bis(ethylbenzothiazoline-6-sulfonic acid) (ABTS). Methanol-pigmented crude extract of P. haeundaensis SAB E11 exhibited the best DPPH scavenging activity with an IC50 value of 54.7 mg/mL, while the n-hexane crude pigment extract of the bacterium reduced ABTS optimally with an IC50 value of 24.46 mg/mL. The analysis of antioxidant compounds in P. haeundaensis SAB E11 was identified by combining liquid chromatography with tandem mass spectrometry (LCMS/MS). The five antioxidant compounds from methanol and n-hexane crude pigment extract of P. haeundaensis SAB E11 have been detected. Polyphenols were found to be the major compound, such as 3,5,3’,4’-tetrahydroxystilbene, scopoletin, and liquiritigenin. The other compounds were dihydroactinidiolide (terpenes) and ricinoleic acid (a fatty acid compound). The orange-colored extract of marine bacterium P. haeundaensis SAB E11 could be promising pharmacological capabilities as an antioxidant.